Pendampingan Guru PAUD dalam Penguatan Literasi melalui Pengembangan Kosakata Berbasis Kearifan Lokal: Teachers in Strengthening Literacy through Local Wisdom-Based Vocabulary Development - Destita Shari; Nanang Rokman Saleh; Muhammad Syaikhon; Berda Asmara; Mujad Didien Afandi (Indonesia Berdaya, 2026)
The limited use of local wisdom as a learning resource, as well as the limited vocabulary introduced to children, has resulted in suboptimal language literacy stimulation for early childhood. This is evident from findings among early childhood education (PAUD) teachers in Pasuruan Regency, who still require guidance in developing children’s vocabulary through the introduction of local wisdom. This community service activity aims to improve early childhood education teachers’ competence in strengthening children’s language literacy through vocabulary development. The activity was attended by 35 early childhood education teachers in Pasuruan Regency. The implementation method consisted of the following stages: needs assessment, presentation of materials, and training on vocabulary development based on local wisdom. Evaluation was conducted through observations and questionnaires completed by the participants. The results of the activity showed that teachers were able to identify vocabulary development sources rooted in local culture—such as regional specialties, arts, and traditions in the area—which were integrated into learning activities. A total of 85% of participants demonstrated improved understanding and skills in designing language literacy activities based on local wisdom. This mentoring program can have a positive impact on enhancing teachers’ competencies in preparing learning experiences to support the strengthening of language literacy among early childhood students.   Abstrak. Rendahnya pemanfaatan kearifan lokal sebagai sumber belajar serta terbatasnya kosakata yang dikenalkan kepada aak menyebabkan stimulasi liteasi bahasa pada anak usia dini belum optimal. Hal tersebut diketahui dari temuan pada guru PAUD di Kabupaten Pasuruan yang masih memerlukan pendampingan kosakata dengan mengenalkan kearifan lokal. Kegiatan pengabdian masyarakat bertujuan untuk meningkatkan kompetensi guru PAUD dalam memperkuat literasi anak melalui pengembangan kosakata. Kegiatan ini diikuti oleh 35 guru PAUD di Kabupaten Pasuruan. Metode pelaksanaan dilakukan melalui tahapan identifikasi kebutuhan, pemberian materi, pelatihan pengembangan kosakata berbasis kearifan lokal. Evaluasi dilakukan melalui observasi, angket yang didapat dari perserta. Hasil kegiatan menunjukkan bahwa guru mampu mengidentifikasi dalam pengembangan kosakata yang bersumber dari budaya lokal seperti makanan khas daerah, kesenian, tradisi diwilayah yang diintegrasikan pada kegiatan pembelajaran. Sebanyak 85% menunjukkan peningkatan pemahamam dan keterampilan dalam merancang aktivitas literasi berbasis kearifan lokal. Kegiatan pendampingan ini dapat memberikan dampak positif terhadap peningkatan kompetensi guru dalam mempersiapkan pengalaman belajar untuk mendukung penguatan literasi anak usia dini